Surgical treatment of far lateral lumbar disc herniation: a safe and simple approach with microscope - محفوض, مفيد (Latakia University Journal -Medical Sciences Series, 2023)
The surgical treatment of Far lateral disc herniation FLDHs has remained a taxing procedure for many spine surgeons due to the inherent difficult anatomical access to the lateral interpedicular compartment without fear of causing nerve damage, or damaging the overlying facet joint, which may place the patient at risk of an unstable spine necessitating spinal fusion surgery in the future. Surgeons therefore often hesitate in offering surgery and rely on conservative therapy in the treatment of FLDHs. This article describes a safe and simple surgical approach for FLDHs and we hope others may find FLDH cases less challenging than the straightforward centrally or para-centrally herniated discs. Methods: 18 patients who harbored Far lateral disc herniation without neurological complications refractory to at least 5 days of conservative treatment were included in this study. Follow-up evaluations included pain (assessed with the visual analog scale [VAS]) and medication use. Functional outcome were measured using ODI (Oswestry low back pain disability questionnaire) were also collected. Results: A significant reduction in pain was found in all follow-up assessments, compared to preoperative values ​​(P<0.001). The average VAS (back pain) score before surgery, was 8.05 (±1.23) and improved after surgery to a score of 3.39 (±1.6) P-value <0.001, 1.39 (±1.02) P-value <0.001, and 1.18 (±1.09)) - P-value <0.001- at first follow-up, second and third follow-up, respectively. The average preoperative ODI score was 33.45 (±6.97) and improved postoperatively to a score of 4.47 (±2.41), p-value <0.001 at the third follow-up. Conclusion: In our experience, the lateral pars interarticularis method for FLDH can be performed safely using this simple approach. We hope that this methodology can instil greater confidence for the surgeon and decrease the anxiety associated with the common lack of familiarity with this region. This ultimately will help to treat patients in a timelier manner, resulting in better outcomes. This technique involves minimal bone-work and if performed together with an intramuscular approach, it may result in less postoperative pain and a reduced length of hospital stay.